Impact of overnight oximetry findings on cardiac autonomic modulation in women during second trimester of uncomplicated pregnancy. Issue 5 (29th December 2014) - Watanabe, Minako; Shinohara, Hitomi; Kodama, Hideya
Abstract Aim Although sleep‐disordered breathing (SDB) might impose an underlying health threat upon some pregnant women, the influence of SDB on the health status of most pregnant women is not discernible. In order to find out which pregnant women should be evaluated for clinically meaningful SDB during the second trimester, the present study aimed to determine which overnight oximetry findings significantly affect maternal resting cardiac autonomic modulations. Material and Methods Overnight arterial oxygen saturation (SaO2) was monitored at home using pulse oximetry by 64 women with uncomplicated pregnancy between 24 and 28 weeks of gestation. We then determined the impact of the findings on maternal resting heart rate variability (HRV) using 5‐min photoplethysmography. Results A relatively increased oxygen desaturation index (number of oxygen desaturation events where SaO2 fell >3% below the baseline saturation/h) of ≥3.0 in five women did not significantly impact HRV. On the other hand, events associated with profound oxygen desaturation (minimum SaO2 ≤ 90%) in three women were associated with decreased HRV, including high‐ and low‐frequency powers. Conclusion Parasympathetic activities of cardiac autonomic modulations might be attenuated in women who experience profound night‐time oxygen desaturation, even if the incidence of significant events is quite low. The oximetry finding of minimum SaO2 ≤ 90% might be a valuable criterion for clinically meaningful sleep‐disordered breathing among women with early uncomplicated pregnancy.